ESTIMASI PARAMETER GENETIK PADA UJI KETURUNAN Alstonia scholaris UMUR DUA TAHUN DI GUNUNGKIDUL, YOGYAKARTA - Mashudi Mashudi; Liliana Baskorowati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2015)
Estimates of genetic parameter were observed at two years old of Alstonia scholaris progeny trial in Gunungkidul, Yogyakarta. The experimental design of the trial was laid out in Randomized Complete Block Design consisting of 48 families, 5 replications, 4 tree-plot and spacing of 4 x 2 meters. This study is aimed to observe the growth variation (height and stem diameter) and the estimates of heritability and genetic correlation among the two growth traits. The results of study showed that the tested families were significantly different for height and stem diameter. The estimate of individual heritability was high at around 0.53 and 0.44 for height and stem diameter, respectively. While the corresponding of family heritability was at around 0.67 and 0.63 for height and stem diameter, respectively. Positive and strong genetic correlation were found between height and stem diameter of this species at two years of age (rg = 0.94).